2020
DOI: 10.1016/j.mayocp.2020.07.024
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Sex Differences

Abstract: Men are consistently overrepresented in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, and coronavirus disease 2019 (COVID-19) severe outcomes, including higher fatality rates. These differences are likely due to gender-specific behaviors, genetic and hormonal factors, and sex differences in biological pathways related to SARS-CoV-2 infection. Several social, behavioral, and comorbid factors are implicated in the generally worse outcomes in men compared with women. Underlying biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
146
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(168 citation statements)
references
References 168 publications
(189 reference statements)
16
146
0
6
Order By: Relevance
“…We found that risk of fatal or critical care unit-treated COVID-19 in diabetes rose steeply with age and was higher in males, as has been reported in many other populations. 28 More than a third of people with diabetes who developed fatal or critical care unit-treated COVID-19 lived in residential care homes, emphasising the crucial importance of protecting such vulnerable individuals during the remainder of this pandemic. There was a strong socioeconomic gradient.…”
Section: Discussionmentioning
confidence: 99%
“…We found that risk of fatal or critical care unit-treated COVID-19 in diabetes rose steeply with age and was higher in males, as has been reported in many other populations. 28 More than a third of people with diabetes who developed fatal or critical care unit-treated COVID-19 lived in residential care homes, emphasising the crucial importance of protecting such vulnerable individuals during the remainder of this pandemic. There was a strong socioeconomic gradient.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Haitao et al on the mechanisms by which biological sex can influence the prognosis of COVID-19 disease concluded that the greater severity and mortality in men compared to women is most likely due to a combination of factors: on the one hand, differences regarding behavior and lifestyles and, on the other hand, comorbidities that affect men to a greater extent. They conclude that biological sex differences could affect the risk of contracting the disease, its physiopathogenic mechanisms, and its severity due to, among other causes, the fact that men are more likely to develop the dreaded cytokine storm associated with a higher lethality of the virus [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…chromosomes, sex steroids) or gender aspects (e.g. social behavior) 8 . Sex differences of genetic origin are constant throughout life, while sex differences originating from hormonal effects may alter with increasing age.…”
Section: Introductionmentioning
confidence: 99%